Kajian Pengelolaan Hutan Mangrove Di Desa Pulau Pahawang Kecamatan Marga Punduh Kabupaten Pesawaran - Rynaldo Davinsy; Asihing Kustanti; Rudi Hilmanto (Jurnal Sylva Lestari, 2015)
Sustainable of mangrove forest management is a proper activity in land and forest product utilization at the coast area. This activity is decent step to relieve mangrove ecosystem demage and preserve it. The circumstances and the factors influenced mangrove forest still needs to be known for the continued in management. The purposes of this study were to determine how the mangrove forest management and development strategy of mangrove forest management. This study was conducted by interviewing the relevant agencies and key informans in the village of Pahawang island from January-April 2015. Datas processing was analyzed by SWOT and descriptive. Result showed that mangrove forest management in good enough with aggressive score (1,22 ; 0,73), which means this strategy gives priority to immediate action by exploiting chances and maintaining strength (growth oriented strategy). Development strategy in the management have to support each other between relevant agencies, the managers, and society. Besides, tracking mangrove development has to be conducted considering the good forest potentials, with the existence of village regulations, and good response from society towards this plan. The strategy should be done by involving Mangrove Protected Area Management Agency and community to optimalize the development. Sustainability of mangrove forest management, should be accompanied with the advanced knowladge of management. Other priority development is by giving counseling, expert-accompanied training, and efficient technological development. Keywords: SWOT, sustainability, strategy of development